Effect of Al addition on oxidation behavior of Nb-based refractory alloys - Xiaolong Li; Yufei Zhao; Linwei Zhang; Qiang Hu; Huahai Mao; Sheng Guo (AIP Advances)
The development of ultrahigh-temperature Nb-based refractory alloys is driven by the quest to further boost the energy efficiency of gas turbines. In terms of material requirements for ultrahigh-temperature applications, high strength at high temperatures, reasonable ductility at room temperature, and decent oxidation resistance are most critical. Unfortunately, meeting these three material requirements simultaneously is highly challenging, and in almost all scenarios, satisfying one requirement is at the cost of jeopardizing the other one or two. Comparatively, more research studies are dedicated to high-temperature strength, room-temperature ductility, and their trade-off, while less attention has been given to oxidation resistance. Here, in this work, improving the oxidation resistance of Nb-based refractory alloys is the focus. In particular, the effect of Al addition on the oxidation behavior of some newly developed Nb-based refractory alloys, Nb79.5−xHf15W5.5Alx (x = 4, 8, 12, at. %), was investigated and benchmarked using the commercial WC3009 alloy. Noticeably, the oxidation resistance of these newly developed Nb-based refractory alloys is much superior to that of the benchmark WC3009 alloy. Although pesting is observed basically in all tested oxidation conditions, suggesting the formation of non-protective oxide scales, the oxidation resistance of Nb-based refractory alloys is significantly improved due to the beneficial effect of Al addition.